The HunchBack of Notre Dame - The Walt Disney Conpany (Brainwaves Limited, 1996)
Timeless Classics--designed for the struggling reader and adapted to retain the integrity of the original classic. These classic novels will grab a student's attention from the first page. Included are eight pages of end-of-book activities to enhance the reading experience.
Keywords: Children Fiction Book